ANALISIS PENGARUH PROMOTION, DISTRIBUTION, PRODUCTION DAN RAW MATERIAL SUPPLY TERHADAP PENINGKATAN KINERJA UMKM KOTA BENGKULU - Lega Gustiana; Islamuddin Islamuddin (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2022)
The purpose of this research is to determine the effect of promotion, distribution, production and raw material supply on improving the performance of SMEs in Bengkulu City. This research was conducted in the food sector SMEs Jl. Anggu City of Bengkulu. The sample in this study was 50 MSMEs with the sampling technique in this study was total sampling. The data collection techniques were observation, questionnaires and documentation. The data analysis technique used in this study was descriptive quantitative. The results show that Promotion individually has an effect on increasing the performance of MSMEs. Distribution individually has an effect on increasing the performance of MSMEs. Production individually has an effect on increasing the performance of MSMEs. Raw material supply individually has an effect on increasing the performance of MSMEs. Promotion, distribution, production and raw material supply simultaneously affect the performance of MSMEs. Keywords: Promotion, Distribution, Production, Raw Material Supply, MSMEs Performance